Formation of Ti3AlC2 MAX phase in the Ti–Al–C system with B2O3 additive - Alexander Rud; Inna Kirian; Yuriy Zagorodniy; Vladimir Trachevski; Mykola Skoryk; Andrey Lakhnik; Victor Voynash (Open Ceramics, 2024)
The main stages of the formation of the Ti3AlC2 in the Ti–Al–C system and the effect of the low-melting additive B2O3 on the yield of the MAX phase were studied by the 13C, 27Al and 47,49Ti Nuclear Magnetic Resonance (NMR) and XRD analysis. The B2O3 addition reduces the synthesis temperature of the MAX phase to 1435 °C. However, the maximum yield of the MAX phase is only ∼72 wt%. NMR spectra for the samples synthesized under non-optimal conditions for the MAX phase formation show the presence of the TiC carbide and aluminium in the metallic state. Both XRD and NMR ways affirm that the borates formation in all samples changes the fraction of aluminium engaged in the MAX phase synthesis and, as a result, reduces the MAX phase yield prepared using B2O3.